2017
DOI: 10.4209/aaqr.2015.05.0331
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Size-Segregated Bioaerosols at Different Sites in Delhi

Abstract: Ambient levels of culturable bioaerosol were measured at four different sites of Delhi, India in six size ranges (> 7.0 µm, 7.0-4.7 µm, 4.7-3.3 µm, 3.3-2.1 µm, 2.1-1.1 µm, < 1.1 µm). The study also accounted the seasonal variation (monsoon, post monsoon, winter and pre-monsoon) of the air microbes. The sampling was carried out for three different fractions of bioaerosols viz. fungi, gram positive and negative bacteria during August 2010 to April 2011 using a six-stage viable cascade impactor sampler. Unlike g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Thus, our study has shown that the average indoor temperature was approximately 30°C and 54% for humidity in the houses of asthmatic children, which represents favorable conditions for mold growth in indoor environments. Additionally, our results have clearly indicated that there is a strong correlation between the number of CFU m -3 and temperature indoor environments, in particular Penicilliumgenre members, as cited in the literature (Pakpour et al, 2015;Lal et al, 2017). We have also demonstrated that there are highly significant correlations between some fungi (including Aspergillus and Mucor) and humidity recorded in the visited houses because it is well known that fungi generally require moisture to grow and sporulate.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, our study has shown that the average indoor temperature was approximately 30°C and 54% for humidity in the houses of asthmatic children, which represents favorable conditions for mold growth in indoor environments. Additionally, our results have clearly indicated that there is a strong correlation between the number of CFU m -3 and temperature indoor environments, in particular Penicilliumgenre members, as cited in the literature (Pakpour et al, 2015;Lal et al, 2017). We have also demonstrated that there are highly significant correlations between some fungi (including Aspergillus and Mucor) and humidity recorded in the visited houses because it is well known that fungi generally require moisture to grow and sporulate.…”
Section: Discussionsupporting
confidence: 50%
“…Bioaerosols generated from airborne particles of biological origin include fungi, bacteria, viruses, and fragments of the foregoing or their metabolic products (e.g., endotoxins, mycotoxins) (Chow et al, 2015;Walser et al, 2015;Chen et al, 2016;Zhang et al, 2016;Lal et al, 2017). Environmental health studies have indicated that constant exposure to bioaerosols containing high concentrations of bacteria can lead to respiratory diseases including allergies, infections, and other adverse health effect (Bünger et al, 2007;Lu et al, 2016;Mirhoseini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bioaerosol, especially airborne bacteria and fungi, is an important concern for indoor environments (Lal et al, 2017). Human exposure to airborne bacteria and fungi can lead to serious infectious diseases (Cole and Cook, 1998;Daniels et al, 2016;Fan et al, 2017;Kim et al, 2017) such as Legionnaires' disease (Berrington and Hawn, 2013), tuberculosis (TB) (Pedersen et al, 2016) and pneumonic plague (Hammamieh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%